Incidence, predictive factors and severity of methotrexate-related liver injury in rheumatoid arthritis: a longitudinal cohort study. Issue 2 (5th June 2020) - Mori, Shunsuke; Arima, Nobuyuki; Ito, Masahiro; Ueki, Yukitaka; Abe, Yasuyo; Aoyagi, Kiyoshi; Fujiyama, Shigetoshi
Abstract: Objectives: The aims were to determine the incidence rate, predictive factors and severity of liver injury that develops during MTX treatment for RA and to evaluate the role of pretreatment hepatic fat deposition. Methods: We used an ongoing real-life registry containing RA patients who had started MTX between August 2007 and April 2018 at participating institutions. The liver-to-spleen attenuation ratio on CT scans at enrolment was used to evaluate pretreatment fat deposition quantitatively. Patients were followed until persistent transaminitis developed or until the end of the study. Liver biopsy was performed for patients who presented with persistent transaminitis. Results: We followed 289 new MTX users without pretreatment elevations of transaminases (mean follow-up time, 58.3 months). Hepatic fat deposition was detected in half of the patients at enrolment. During follow-up, persistent transaminitis occurred at a crude incidence rate of 3.13 per 100 person-years, and the cumulative incidence at 5 years was estimated to be 13%. A multivariate Fine–Gray regression analysis showed that the most important predictive factors were pre-existing moderate to severe fat deposition (adjusted hazard ratio, 7.69; 95% CI: 3.10, 19.10) and obesity (adjusted hazard ratio, 2.68; 95% CI: 1.37, 5.25). Non-alcoholic steatohepatitis (NASH) was the most predominant pattern in liver biopsy samples. Hepatic fibrosis was found in 90% of samples, but most cases were not advanced. Conclusion: Aggravation of underlying fatty liver to NASH with fibrosis seems to be an important mechanism of liver injury that occurs in MTX-treated RA patients.